Deterioração da madeira de piptadenia moniliformis benth. E pinus sp. Pela podridão branca e parda em ensaios de laboratório - Silva, Françóyse Dávilla de Souza (Universidade Federal Rural do Semi-Árido, 2020)
Timbers, from softwood or hardwood, have their own natural resistances in the face of xylophagous microorganisms' actions that affect their physical, chemical and biological properties. The Caatinga is a biome abundant in species diversity, however, it isn't immune to the basidiomycetes actions. Due to this, this work aimed to evaluate the natural resistance of Piptadenia moniliformis Benth. (Catanduva) wood, a Caatinga native species, and also Pinus sp. wood in order to analyze the attack made by Ganoderma sp. fungi (responsible for white rot) and Daldinia sp. fungi (responsible for brown rot). Specimens from each species were prepare for laboaroty test, submitted to the following treatments: T: control sample; T1: Ganoderma sp.; T2: Daldinia sp. placed in cooling system type B.O.D, temperature of 28°C during 18 weeks. Among the studied species, it was possible to observe that values of weight loss for Cantanduva were higher than the ones of Pinus, average weight loss of 8,57% when attacked by white rot and 7,12% by brown rot. However, it was possible to conclude that even though the statistical difference between species, according to Tukey test at 5% significance level, both were highly resistant to white and brown rot fungi attack
Keywords: Perda de massa; Celulose; Degradação; Madeira; Weight loss; Cellulose; Degradation; Wood; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL